2022
DOI: 10.1097/bsd.0000000000001330
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fusion Rate and Functional Outcome Between Local Cancellous Bone Plus Demineralized Bone Matrix and Local Bone in 1-Level Posterior Lumbar Interbody Fusion

Abstract: Study Design: Retrospective study with prospectively collected data. Objective: The purpose of this study is to investigate the difference in fusion rate and clinical outcome of patients with local bone as filler for the graft and demineralized bone matrix (DBM) plus only the cancellous bone from local bone as a filler for cage in 1-level posterior lumbar interbody fusion (PLIF) with cage. Summary of Background Data: Cancellous bone is more advantageous than cortical bone in the local bone for improving bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…The achievement of a fully solid fusion mass is crucial for the positive outcomes and success of lumbar interbody fusion surgery [13][14][15]. Previous literature indicates a radiologic fusion rate for PLIF ranging from 71% to 96% [11,16,17]. Autologous iliac bone graft is considered the gold standard for PLIF surgery [18], but it carries the risk of complications such as donor site morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The achievement of a fully solid fusion mass is crucial for the positive outcomes and success of lumbar interbody fusion surgery [13][14][15]. Previous literature indicates a radiologic fusion rate for PLIF ranging from 71% to 96% [11,16,17]. Autologous iliac bone graft is considered the gold standard for PLIF surgery [18], but it carries the risk of complications such as donor site morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…In a canine study, the combination of DBM with autograft demonstrated faster spinal fusion compared to autograft alone, and in a rabbit interbody fusion model, a composite graft of DBM and hydroxyapatite block exhibited quicker and stronger fusion than autograft alone [9,10]. Furthermore, numerous human studies have demonstrated that the utilization of DBMs is an effective choice for bone union in PLIF surgery [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed that older age and decreased bone density were associated with lower rates of fusion in both groups. Most recently, Ko et al 50 found that in 40 patients undergoing singlelevel PLIF (20 DBM and 20 local autograft), there was improvement in Brantigan-Steffee fusion scores in patients receiving DBM (4.4 DBM vs 3.7 local autograft, P = 0.001) but no difference in ODI between groups.…”
Section: Lumbar Spinementioning
confidence: 99%
“…There are adverse effects beyond those expected because there may be postoperative complications since the commonly used procedures are very invasive [2]. Lumbar fusion has been the standard procedure for patients with lumbar disc wear that does not respond to conservative treatments, with excellent clinical results [12][13][14].…”
Section: Introductionmentioning
confidence: 99%